Increasing the investment attractiveness of the republic of Uzbekistan: results, problems, prospects. - NADIRKHANOV, UBAYDULLA S. (The journal of contemporary issues in business and government, 2021)
Attracting foreign investment, since the first economic reforms, has always been the focus of the government of the Republic of Uzbekistan. The article considers investment processes in retrospect, substantiates measures to increase investment attractiveness. Particular attention is paid to the organization and management of foreign investment processes in 2015- 2020, including the development of legal and organizational frameworks regulating the attraction of foreign investment and their protection.